h/6=12/7/2

Simple and best practice solution for h/6=12/7/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h/6=12/7/2 equation:


h in (-oo:+oo)

h/6 = (12/7)/2 // - (12/7)/2

h/6-((12/7)/2) = 0

h/6-6/7 = 0

1/6*h-6/7 = 0 // + 6/7

1/6*h = 6/7 // : 1/6

h = 6/7/1/6

h = 36/7

h = 36/7

See similar equations:

| =-8(10r^2-5r)+8(7r^2+7r) | | 8y^2+57y+7=0 | | 0.01(5x+4)=0.3-0.3x | | 0.8w-0.4=-5+w | | Y=3/z | | -10x^2-41x-21=0 | | 3r+4=28 | | 8=3p+25 | | 40x^2+90x+45=0 | | 4x^5+22x^4+10x^3=0 | | 28+2y-10=12y-12-4y | | 3.2(x+1.5)=2.4x-2.7+1.4x | | 6y-3x=10 | | 3x+8x=60 | | 3x-x/3+x+1/7=4x | | -3(-4+x)=27 | | -7+5x+7x=-139 | | 2/(5w-30)+2=6/(w-6) | | 175000+550.00x=220650.00 | | -4/(2x+12)+3=-2/(x+6) | | 4(-10+7x)=-264 | | 7/(y-6)=5/(4y-24)-2 | | 35000+1680.00x=300.440 | | -7/(5x+5)+1=-5/(x+3) | | 6h+19h=2 | | 5(1+4)-(5*1+20)=0 | | 4/(w+4)=8/(2w+8)-3 | | 7(8+3y/5)-3y=-10 | | 6h+19forh=2 | | -6/(y+2)=2/(3y+6)-1 | | 7(8+3y/5) | | |-2n|=6 |

Equations solver categories